COVID-19 vaccinations and the volatility of energy companies in international markets - Ender Demir; Renatas Kizys; Wael Rouatbi; Adam Zaremba (Journal of Risk and Financial Management, 2021)
The COVID-19 pandemic has elevated both the risk and volatility of energy companies. Can mass vaccinations restore stability within this sector? To answer this question, we investigate stock market data from fifty-eight countries from January 2020 to April 2021. We document that vaccination programs assist in decreasing the volatility of energy stocks around the world. The drop in volatility is statistically and economically significant and robust to many considerations. The observed phenomenon survives a broad battery of control variables; it is also independent of the employed regression model or the volatility measurement approach. Moreover, the effect is not driven by the dynamics of the pandemic itself or the associated government interventions. Finally, we find the influence of vaccinations on energy stock volatility to be more pronounced in developed markets rather than in emerging ones. Our findings bear clear practical implications: policy makers around the world should consider the essential role of vaccinations in the energy sector.
Keywords: 330; COVID-19 pandemic; vaccinations; stock market volatility; energy companies; coronavirus; international equity markets